1996
DOI: 10.1007/bf00400671
|View full text |Cite
|
Sign up to set email alerts
|

High glucose concentration inhibits migration of rat cranial neural crest cells in vitro

Abstract: Cranial neural crest cells give rise to a large part of the facial structures, and disturbed development of these cells may therefore cause congenital malformations affecting the head and face. We studied the effects of increased glucose concentration on the migration and development of cranial neural crest cells, maintained in vitro for 48 h. Pre-migratory cranial neural crest cells were removed from embryos of normal and diabetic rats on gestational day 9. After 24 h in 10 mmol/l glucose the cells were expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…According to previous reports investigating cell migration under high glucose condition, the effect of glucose on cell migration still remains controversial depending on the cell types [14, 44, 45]. Our data in this study revealed that high glucose stimulates hUCB-MSC migration with suppression of E-cadherin expression.…”
Section: Discussionsupporting
confidence: 62%
“…According to previous reports investigating cell migration under high glucose condition, the effect of glucose on cell migration still remains controversial depending on the cell types [14, 44, 45]. Our data in this study revealed that high glucose stimulates hUCB-MSC migration with suppression of E-cadherin expression.…”
Section: Discussionsupporting
confidence: 62%
“…This study demonstrated that exposure to high glucose reduces cell number and inhibits cell migration. [45] This system was also used efficiently to demonstrate the neuroprotective effects of antioxidant N-acetylcysteine and superoxide dismutase against hyperglycemia. [45]…”
Section: Primary Cultures As a Model Systemmentioning
confidence: 99%
“…25 Hyperglycaemia has a direct influence on the proliferation and migration of neural crest cells which are critical in the development of the heart and brain. 26 However, experimental work has shown not only increased glucose values but also that values of triglycerides, b-hydroxybutyrate, branched chain amino acids, and creatinine correlate positively with increased resorption rates and malformation rates among affected pregnancies. 27 Maternal diabetes is associated with induction of placental genes associated with chronic stress and inflammation, 28 and recent investigations have even implicated a potential role for inflammation in the evolution of maternal diabetes-induced embryopathy.…”
Section: Maternal Diabetes and Evolution Of Congenital Heart Diseasementioning
confidence: 99%